Molecular Mechanisms Underlying Activity-Dependent GABAergic Synapse Development and Plasticity and Its Implications for Neurodevelopmental Disorders - Bidisha Chattopadhyaya (Neural Plasticity)
GABAergic interneurons are critical for the normal function and development of neural circuits, and their dysfunction is implicated in a large number of neurodevelopmental disorders. Experience and activity-dependent mechanisms play an important role in GABAergic circuit development, also recent studies involve a number of molecular players involved in the process. Emphasizing the molecular mechanisms of GABAergic synapse formation, in particular basket cell perisomatic synapses, this paper draws attention to the links between critical period plasticity, GABAergic synapse maturation, and the consequences of its dysfunction on the development of the nervous system.